Results of oestrus synchronization in sheep with subcutaneous implants and intravaginal sponges in three different seasons of the year - ΤΣΑΚΑΛΩΦ, Π.; ΤΡΙΚΑΣ, Μ.; ΠΑΡΛΙΤΣΗΣ, Ι.; ΚΑΡΑΓΙΑΝΝΙΔΗΣ, Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
A total of 4694 ewes from 50 flocks were synchronized for oestrus In the prefecture of Piena during 1978. Of these animals, 1618 were synchronized during anoestrus (March-April), 2458 during the transistory period (May-June) and 618 during the breeding -season (July-September). Synchronization was carried out by means of intravaginal sponges (Veramix Upjohn), containing 50 mg of the progestagen MAP and subcutaneous implants (Silestrus Abbot) containing 375 mg progesterone. After withdrawal of the sponges and Implants 14 days later, all animals were injected with 500 Lu. P.M.S. All ewes sere bred naturally. The mean percentage of ewes exhibiting oestrus amounted to 96.66% and fluctuated only slightly between the sponges and implants and among the three breeding seasons. The percentages of conceptions and lambings at the 1s t and at the 1s t and 2 synchronized oestrus showed a progressive improvement from the anoestrus period (56.8%, 51.6% and 73.4%, 66.5%, respectively) to the transistory period (61.9%, 58.4% and 82.2%, 77.3%, respectively) and reached their optimum at the breeding season 70.3%, 66.7% and 86.8%, 82.5%, respectively. Irrespective of the season, the percentage of conceptions and lambings achieved with the implants both at the 1* (57.2%, 52.1%, respectively) and at the la and 2 n d synchronized oestrus (77.7%, 71.2%, respectively) were significantly lower (P<0.01) than those achieved with the sponges (68.0%, 65.6% and 83.3%, 79.3%, respectively), owing to the high percentage of suppurations observed at the site of implant insertion during the transitory period. Because of these suppurations the percentage of conceptions and parturitions achieved with the implants did not show any progressive improvement from the anestrous period (55.8%, 48.7% and 74.0%, 66.0%, respectively) to the transitory period (55.8%, 51.7%, and 78.9%, 73.3%, respectively). Conversely, the percentages of conceptions and lambings achieved with the intravaginal sponges showed a progressive improvement from the anoestrous period (59.3%, 59.1% and 71.9%, 67.6%, respectively) to the transitory period (77.2%, 68.6% and 87.2%, 83.3%, respectively) and were optimum during the breeding season.